Red dust - Fleming, Victor 1883-1949; Mahin, John Lee 1902-1984 (Warner Bros. Entertainment, 2012)
When wisecracking Vantine hides away on Carson's plantation, he sizes her up as an easy target for his charm. But things change when an engineer and his beautiful wife show up and Carson writes Vantine off as nothing more than a 'cute little trick.' Now, with the two women vying for Carson's affection, a rivalry forms that soon boils over into jealousy and violence